EXPERIENTIAL NARRATIVE LEARNING STRATEGIES IN FOSTERING LOVE FOR THE COUNTRY AND SOCIAL CONCERN IN STUDENTS IN PPKN SUBJECTS IN CLASS V SDN 106161 PERCUT SEI TUAN - Wawan Akbar; Deny Setiawan; Anita Yus (SENSEI RESEARCH CENTER, 2022)
This research is a qualitative research with a case study approach. The reason for using case studies is that this research examines existing cases so that researchers only study existing cases. This research will be conducted at SDN 106161 Percut Sei Tuan. The time of this research was carried out in March-April 2022. The total informants needed were 2 fifth grade teachers and 6 students. Determination of informants in this study was done by purposive sampling technique. After describing the results and discussion, the conclusions in this study are determined:1) For the value of patriotism, according to the researcher, the students of SDN 106161 Percut Sei Tuan have a good attitude of nationalism but still don't know much about the values of nationalism that must be fostered. Then students also have social care for fellow friends, family and teachers as well as for surrounding creatures such as animals that pass around the school and the plants that grow around the school are cared for properly. 2) The problem related to social care and love for the homeland lies in the lack of enthusiasm for students showing these 2 characters in learning and the importance of these two attitudes, considering that at present the problem of love for the homeland is very minimal for children because of global influences, technology and the entry of foreign culture into Indonesia so that it affects children. 3) The process of implementing experiential narratives where learning is carried out with the concept of telling the experience of role models in this country related to the Proclamation and Presidents 1 and 2 in Indonesia has been carried out very well